Myofibrillar myopathy: a rare but important differential diagnosis of camptocormia in a patient with Parkinson’s Disease - Jan Niklas Petry-Schmelzer; Angela Abicht; Michael T. Barbe; Gilbert Wunderlich (Neurological Research and Practice, 2023)
Abstract Here we report on a patient with Parkinson's Disease and camptocormia due to Myofibrillar Myopathy Type 3. By leading the reader through the clinical reasoning process and highlighting the respective red flags we aim to increase the readers’ awareness for the differential diagnosis of camptocormia.